(3QjMGf GdCdHGH, hQjYGf GdTHGH, aj eQGJH GdBOGHs - (3eMeO Hf EHQGgje Hf NjQI, CHh GdbGSe Hf GdehGYjfj GdbQWHj GdETHjdj,J (B564 (3g` s ((3YHOGddg Hf eMeO GdYeGQj GddeWi s)
(3ChdgG (B:s
(3QH ChRYfi Gf CTcQ fYeJc GdJi GfYeJ Ydi gPG cJGH febJg HELJeGY GdacQ s
(3BNQgG (B:s
(3aVd GdRgGO hGdeHJdjf, bGd Ydi Hf CHj WGdH(B: (3bfY GdfaS GdcaGa hEdG WdHJ efc ahb eG jcajgG hEfeG GfJ Whd YeQc eGYeQ J ai GdSGYI GdJi CfJ ajgG hGdMeO ddg ced JGdjag s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B198s
Keywords: (3GdCOHs